UTILIZATION OF QGIS CLOUD FOR MAPPING ACCIDENT-PRONE AREAS IN CIREBON CITY - Prayoga, Mohamad Adjie; Umam, Mochammad Putra Mantiqul; Awani, Muhammad Khalsya Noor; Yunanda, Novra; Fadhila, Syawal Badri; Supriyadi, Hari (CENTRAL ASIA AND THE CAUCASUS, 2022)
Cirebon city is one of the cities located in West Java Province, Indonesia. This city is on the northern coast of Java Island or known as the pantura line, this path is one of the lanes that are very high accident-prone. But information related to points or areas that are considered high in accidents cannot be conveyed thoroughly to road users, this is because there is no media that can provide such information. Therefore, in this study conducted analysis and manufacture of mapping of accident- prone areas with QGIS technology which is often known as Geographic Information System (SIG) to plan and provide information sparsely that can provide any point or area that is highly rated accident. The methods used in making this mapping use spiral methods, the process begins with planning, risk analysis, engineering, and evaluation by the user (including planning and management). The results of mapping accident-prone areas in the pantura lanes of Cirebon City can provide different patterns in providing information to road users by utilizing QGIS technology online, to provide convenience for road users to know which points or areas are classified as high accident rates, this can provide warning for road users to be careful in driving.